Perceived senior secondary students' level of computer anxiety and competences in Oyo education zone of Oyo state, Nigeria (2020)
The Nigerian government policy statement on design and development of innovative materials for effective teaching in Nigerian schools is yet to be fully realized because it depends on students' competency in computer and associated technologies. Therefore, this study investigated perceived senior secondary students' level of computer anxiety and competences in Oyo Education Zone of Oyo State, South-West, Nigeria. This baseline study adopted ex-post facto of survey type and purposively selected public secondary schools that are equipped with computer facilities. It involved one hundred and sixty (160) senior secondary schools, one student from four schools including one private school in Iseyin and Itesiwaju Local Government Areas of Oyo Education zone in Oyo State, South-West, Nigeria. Four research questions guided the study with the use of two instruments namely i.e. Students' Computer Anxiety Questionnaire (SCAQ) r=0.86 and Students' Computer Competence Questionnaire (SCCQ) r=0.87. Findings from the study indicated that majority of the participants perceived themselves of having positive disposition to computers, thereby having no computer anxiety. Also, majority perceived that they are skillful in general Window skills, Word processing and presentation software respectively. Therefore, the study recommends exposure of students to practical computer activities during computer studies lessons and effective use of computer facilities where there are provisions. It also recommends adequate provision through the involvement of the parent-teacher association and non-governmental organisations as well as public spirited individuals, where such facilities are lacking.